BREAST SELF-EXAMINATION (BSE) PRACTICES AMONG FEMALE STUDENTS IN HIGHER INSTITUTIONS IN IBADAN: IMPLICATIONS FOR CANCER EDUCATION (1992)
This study assessed the knowledge, attitude and existing breast self-examination practices among six hundred and ninety female students of the University of Ibadan and the Ibadan Polytechnic, Oyo State, Nigeria; using a set of questionnaire. Results showed that 66.1% had ever practiced breast self-examination. However, only 77% reportedly carried out monthly examination of their breasts in the last six (6) months, although 84.6% were aware of it and 33.3% knew that it should be carried out monthly. Knowledge of the correct sequence of breast self-examination and the symptoms to look for was low. The major source of information on breast self- examination was through the mass media. There was a generally positive attitude toward the behaviour. In light of these findings, some breast self- examination information packages and progammes are proposed for the students. In addition, suggestion regarding the examination of breast, self-examination materials for completeness, accuracy and appropriateness before dissemination to the public were made.